1980
DOI: 10.1002/bjs.1800670902
|View full text |Cite
|
Sign up to set email alerts
|

Does β-blockade affect surgical performance?. A double blind trial of oxprenolol

Abstract: Heart rates of surgeons rise when they carry out operations and this rise is abolished by beta-blockade. In an assessment of the effect of oxprenolol on surgical performance a group of surgeons took double blind either oxprenolol 40 mg or a matching placebo. Oxprenolol abolished increases in heart rate (P < 0.001) but had no effect on a profile of performance test assessing tremor, suturing accuracy and co-ordination. Reaction time of the surgeons was significantly slowed by oxprenolol (P < 0.01). Using a self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…Oxprenolol given prior to pistol shooting competitions was shown to be associated with greater subjective calmness and improved shooting performance relative to placebo (9 1) but acebutolol failed to improve performance in rifle shooting (92). Oxprenolol has also been shown to abolish the tachycardia seen in surgeons whilst operating, but in this study (93) there was no alteration of subjective feelings and no changes in tests of tremor and suturing accuracy whilst reaction time was significantly slowed. In general, observed beneficial effects in situational anxiety relate primarily to somatic symptoms, with psychic benefits being less prominent or absent.…”
Section: Phobic Statescontrasting
confidence: 48%
“…Oxprenolol given prior to pistol shooting competitions was shown to be associated with greater subjective calmness and improved shooting performance relative to placebo (9 1) but acebutolol failed to improve performance in rifle shooting (92). Oxprenolol has also been shown to abolish the tachycardia seen in surgeons whilst operating, but in this study (93) there was no alteration of subjective feelings and no changes in tests of tremor and suturing accuracy whilst reaction time was significantly slowed. In general, observed beneficial effects in situational anxiety relate primarily to somatic symptoms, with psychic benefits being less prominent or absent.…”
Section: Phobic Statescontrasting
confidence: 48%
“…They further concluded that the autonomic response to stress could be blocked by oxprenalol without affecting performance adversely. The recent studies of Foster et al (1979) have shown a similar type of response in surgeons while operating and again report that while oxprenalol reduced the heart rate response it did not affect tremor or manual dexterity.…”
Section: Discussionmentioning
confidence: 61%
“…This subjective inability to recognise autonomic blockade has recently been confirmed in studies of the effect of 3 blockade on the performance of surgeons (Foster et al 1979).…”
Section: Stress Responsementioning
confidence: 83%
“…Receiving low-dose propranolol was also associated with shortened time to task completion compared with low-dose caffeine. Foster et al reported a potential confounding effect (ie, increase in time of surgeon’s reaction time after receiving 40 mg of oxprenolol, a different class of β-blocker) but no association with accuracy or tremor.…”
Section: Discussionmentioning
confidence: 99%